Efektivitas Teknologi RAS (Recirculating Aquaculture System) Melalui Pemberian Pakan Artemia (Artemia sp.) Pada Pendederan Ikan Sidat (Anguilla bicolor) Stadia Glass Eel Ke Elver - Gilang Ramadhan; Dasep Hasbullah; Arif Supendi; Adi Gumbara; Deni Rusmawan; Robin Robin; Esa Nur Dzikra; Rifky Alzufri (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2026)
This study aims to determine the effect of administering Artemia sp. feed at different doses on the survival, water quality, and growth of eel (Anguilla bicolor.). The study was conducted using an experimental method with a Completely Randomized Design (CRD), consisting of 3 treatments and 3 replications, analyzed using Analysis of Variance (ANOVA). A total of 14,400 eel juveniles with an initial average length of 4.98 ± 0.01 cm and an initial average weight of 0.138 ± 0.001 g were used as test animals. The treatments applied were different doses of Artemia sp. feed: treatment A (5%), treatment B (10%), and treatment C (15%) of the biomass weight for each treatment. The results showed that feeding Artemia sp. at different doses had no significant effect on survival rate (SR), water quality, or growth, but it significantly influenced the optimization of the water quality of the rearing media. At the end of the study, the survival rates for each treatment were: treatment A 98%, treatment B 99%, and treatment C 98%. The average weight gain in treatment A (5% dose) was 0.875 ± 1.421 g, with an average length increase of 0.237 ± 0.013 cm. Treatment B (10% dose) resulted in an average weight gain of 0.353 ± 0.034 g and an average length increase of 0.156 ± 0.002 cm. Treatment C (15% dose) resulted in an average weight gain of 0.167 ± 0.033 g and an average length increase of 0.243 ± 0.012 cm. Water quality parameters in all treatments remained within optimum conditions, with pH 7.49, temperature 24.0°C, and dissolved oxygen (DO) 6.2 mg/l, which supported the experimental treatments. Keywords : Anguilla bicolor, feed dose, Artemia sp, growth, survival rate.